Acceptability of Pili Pasta - Maria Luisa Gonzales; Sheila Nunez (Philippine Association of Institutions for Research, Inc., 2020)
The study appraised the acceptability of pili pasta in the 2nd District of Albay. It determined the status of pili products in the 2nd district of Albay, Philippines, the level of Acceptability, along with appearance, aroma, texture, and taste, the SWOT analysis and challenges encountered in its production, and Marketability along with the product, promotion, price, place and people, likewise, the signed agreement on the rank order of its Acceptability and Marketability. It is substantial to the Department of Tourism (DOT), food industry, culinary professors, and culinary students. It used descriptive-inferential and experimental methods in determining the responses from 176 respondents in 4 groups. Findings revealed that the most known pili products are sweets and candies. The product was analyzed using the SWOT analysis and is highly acceptable in terms of appearance, aroma, texture, and taste. It was also considered marketable for its product, promotion, price, place, and people. The four groups of respondents significantly agreed on the Acceptability of pili pasta when it comes to taste. While they disagree significantly concur on its Marketability for the reason that different categories of respondents have different perspectives when it comes to marketing strategy to use in promoting the product. Therefore, pili pasta is acceptable defending in its location of marketing it.